Prevalence of IgG-4-associated cholangiopathy based on serum IgG-4 levels in patients with primary sclerosing cholangitis and its relationship with inflammatory bowel disease - Taghavi, Seyed Alireza; Majd, Shaghayegh Kaedi; Sianati, Mahnoosh; Sepehrimanesh, Masood (Turkish Journal of Gastroenterology, 2016)
Abstract Background/Aims: Autoimmune cholangiopathy is part of a fibro-inflammatory immunoglobulin G-4 (IgG-4)-related systemic disease that causes biliary tract strictures. Its clinical presentation is quite similar to that of more common diseases such as primary sclerosing cholangitis (PSC) and pancreatobilliary malignancies. The aims of the present study were to evaluate the prevalence of IgG-4-associated cholangiopathy (IAC) in patients diagnosed with PSC and its relationship with inflammatory bowel disease (IBD). Materials and Methods: Serum IgG-4 levels were measured in 73 patients. Laboratory data and imaging and endoscopic results were collected from their medical records. The diagnosis of PSC was based on the results of imaging and laboratory data as well as clinical presentation. Results: Serum IgG-4 levels were elevated in 12 patients (16%); half of these patients had IBD. In the group of patients with normal serum IgG-4 levels, 39 patients (63.9%) had IBD (p=0.364). There were no significant statistical differences between PSC patients with normal and elevated serum IgG-4 levels in terms of age, smoking, presence of IBD, extension and severity of IBD, esophageal and gastric varices, Child and the model for end-stage liver disease (MELD) scores, and anatomical location of the biliary stricture (p>0.05). The prevalence of ascites was higher in patients with elevated serum IgG-4 levels (p=0.029). Conclusion: Compared with previous reports, high serum IgG-4 levels were detected in a higher percentage of patients with a preliminary diagnosis of PSC (12% versus 16%). However, there were no clinical or imaging characteristics that could differentiate PSC patients with normal IgG-4 levels from PSC patients with higher IgG-4 levels.